2013
DOI: 10.1249/mss.0b013e31829406c7
|View full text |Cite
|
Sign up to set email alerts
|

Quiet Eye and Choking

Abstract: Performance failure under pressure appears to be due to disruptions in attentional control once movement has been initiated. These findings support the predictions of attentional control theory and suggest that the QE may have an online control function, providing visual sensory information as the movement unfolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 36 publications
9
57
2
2
Order By: Relevance
“…To further advance our understanding of the processes underpinning this relationship, we sought to test a three-stage model: Does goal-directed planning further mediate this perception-performance effect? Specifically, we predicted that biases in the perception of the target hole would influence subsequent motor planning (Glover, 2002) that occurs while the performer fixates the ball (Vickers, 1992), and that this, in turn, would bias performance (Moore et al, 2012;Vickers, 1992;Wilson & Pearcey, 2009;Vine, Lee, et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further advance our understanding of the processes underpinning this relationship, we sought to test a three-stage model: Does goal-directed planning further mediate this perception-performance effect? Specifically, we predicted that biases in the perception of the target hole would influence subsequent motor planning (Glover, 2002) that occurs while the performer fixates the ball (Vickers, 1992), and that this, in turn, would bias performance (Moore et al, 2012;Vickers, 1992;Wilson & Pearcey, 2009;Vine, Lee, et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…The quiet eye was operationally defined for golf putting as the final fixation toward the ball prior to the initiation of the backswing, and its duration as the time between the onset and offset of this fixation (as in Moore et al, 2012;Vickers, 2007;Vine, Lee, Moore, & Wilson, 2013a;Wilson & Pearcey, 2009). Quiet eye onset occurred before the backswing began, and quiet eye offset occurred when the gaze deviated off the ball location by 1º or more for greater than 100 ms.…”
Section: Methodsmentioning
confidence: 99%
“…For the subcomponents of the quiet eye period, no outcome-related differences were predicted for QE-preprograming (Vine et al 2013), whereas longer durations of QE-online (Vine et al 2013) and QE-dwell (Vickers 1992, 2004, 2007; Vine et al 2013) were predicted for low-RE compared to high-RE putts. With regard to the role of preprograming, it is predicted that the longer putts will require longer QE-preprograming duration compared to shorter putts (Williams et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In golf putting, it is thought that an effective quiet eye period consists of: (1) a single, long, continuous fixation on the back of the ball; (2) an onset before backswing; (3) a continued fixation through the backstroke, forestroke and contact; (4) a dwell time after contact (Vickers 2007; Vine et al 2013). It is suggested that prioritising task-relevant visuo-spatial information for skill execution during the final fixation leads to a reduction in cortical resources associated with analytical processing and attention to irrelevant sensory cues (Vickers 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, current approaches 7 to training gaze patterns have emphasised investigation of universal 'optimal' search strategies 8 for a given task [5,6]. In contrast, a number of coordination researchers have proposed a 9 requirement to move away from 'one-size fits all' interventions towards understanding of 10 how individualised movement patterns emerge for a given task [7]. Thus, at face value, there 11 are two different conceptualisations of expertise and learning in the perceptual-motor 12 literature.…”
Section: Introductionmentioning
confidence: 99%